Representasi Mitologi Gunung Lawu dalam Novel Aroma Karsa Karya Dee Lestari - Annisa Annisa (Gondang: Jurnal Seni dan Budaya, 2018)
The myths and cultures associated with Mount Lawu. The most mysterious mountain and save a million mysteries in Java. Myths and culture that evolved into a puzzle in the novel Aroma Karsa by Dee Lestari which is interesting to explore more and so real depictions. This study aims to get an overview of the myths and culture of the people on the slopes of Mount Lawu that are in effect. This research is content analysis using a literary anthropology approach. Data sources were from Aroma Karsa's novel by Dee Lestari. The results of this study are depictions of myths and cultures in the form of (1) myths and culture through the location of the place or location, (2) myths and culture through the techno-economic owner's community, (3) myths and culture through the sociology of the owner's community, (4) and myths of culture through cosmology. The depiction of myths and culture has a conservation impact or still preserves the heritage of the ancestors of the community on the slopes of Mount Lawu. Knowing human relationships with other creatures created.